Społeczne uwarunkowania kształtu i przemian świadomości klasowej polskiej klasy robotniczej - Ziółkowski, Marek (Wydział Prawa i Administracji UAM, 1987)
The article outlines a theoretical perspective for analyses of the consciousness of Polish working class in the last decade and comments on some available results of empirical studies. The workers' consciousness may be analysed in three rather differents phases: 1) the late 70, 2) 1980-81, 3) since 1982-83. Each of them is characterized by different relations between 1) basic values and ideals held by workers, 2) their perception, evaluation and explication of the present state of affairs and 3) their dispositions to individual and collective behaviour. The article presents an increase and subsequent gradual extinction of radical ("revolutionär') consciousness and the accompanying sociopsychical processes.
Social Conditions of the Contents and Changes in Class Consciousness of the Polish Working Class